Social Workers Dealing with Ethical Dilemmas in the Course of Their Professional Work: The Greek Experience. (10th May 2022) - Chatzifotiou, Sevaste; Papouli, Eleni
Abstract: Globally, ethical dilemmas are a relatively neglected topic in social work research, despite their obvious importance to ethical professional practice. This study aims to contribute to the existing literature by exploring ethical dilemmas and related issues faced by social workers in Greece. For our purposes, we created an online survey questionnaire via Survey Monkey software and distributed it nationwide to all social workers, asking those who had more than two years of work experience at any kind of service providing agency to complete it. A total of 835 questionnaires were returned and used for data analysis (response rate 11.13 per cent). The study highlights the diversity of ethical dilemmas encountered by social workers in their professional practice, as well as revealing the different strategies, tools and mechanisms used in dealing with them. Further, it shows the urgent need for developing appropriate ethics support activities and training programmes for social workers, as a crucial part of their ongoing professional education and development. Such ethics initiatives are required to remain ethically competent throughout their working life. Abstract : In most countries, including Greece, ethical dilemmas are a relatively neglected research topic in social work, despite their obvious importance to ethical professional practice. The purpose of this study is to provide a contribution to social work empirical studies by examining ethical dilemmas and related issues facing social workers in Greece. A total of 835 online questionnaires were collected and used for data analysis (response rate 11.13 per cent). The study highlights the diversity of ethical dilemmas encountered by social workers, as well as the ways and means they have at their disposal to manage them effectively. Further, it shows the urgent need for developing appropriate ethics support activities and training programmes or/and courses (face to face or/and online courses) for all social workers, regardless of their professional setting, as a crucial part of their ongoing professional education and development. As evidenced in this study, ethics support and training initiatives should be a crucial part of the continuing professional development of social workers in order to be considered ethically competent throughout their working life, as well as keeping their knowledge and skills up to date.